Recreating the past in the ornamentation of stately homes and the leisure activities conducted within them: the Duchess of Parcent as a case study for the Spanish aristocracy in the early twentieth century. Issue 2 (4th May 2019) - Ramos Frendo, Eva María
ABSTRACT: This paper attempts to vindicate the part played by certain Spanish aristocratic women in the management, conservation, and transmission of their artistic patrimony in the decades around the turn of the twentieth century by creating art collections and displaying them in their own homes. The works were exhibited in rooms that were decorated and furnished to suggest historical ambiences in which French trends rubbed shoulders with styles that had been developed in Spain throughout its history, turning their homes into devices that recreated past times. Similarly, retrospective views of Spanish art were the focus of leisure and entertainment activities driven by ladies from the upper echelons of society through the performance of tableaux vivants . The focus of this study will be Trinidad Scholtz Hermensdorff, Duchess of Parcent.